2023
DOI: 10.1183/23120541.00569-2022
|View full text |Cite
|
Sign up to set email alerts
|

Application of the Rome severity classification of COPD exacerbations in a real-world cohort of hospitalised patients

Abstract: BackgroundRecently, the Rome classification was proposed in which objective and readily measurable variables were integrated to mark exacerbations of COPD (ECOPD) severity. The aim of this study is to investigate the distribution of a real-world patient population with hospitalized ECOPD according to the current classification across the newly proposed severity classification. We assume that a significant proportion of hospitalized patients will have a mild or moderate event.MethodsThe Rome classification was … Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
1
1

Citation Types

0
5
0

Year Published

2023
2023
2024
2024

Publication Types

Select...
8

Relationship

0
8

Authors

Journals

citations
Cited by 8 publications
(9 citation statements)
references
References 40 publications
0
5
0
Order By: Relevance
“…Firstly, due to our study design, it remains uncertain to what extent patients with a severe AECOPD had impairments in physical status before hospitalization. Secondly, after finalization of our study, the ROME proposal suggested an alternative classification of exacerbation severity 54 . However, we have not evaluated the specific parameters utilized in the ROME classification, leaving us uncertain about the prevalence of mild or moderate exacerbations among our patients.…”
Section: Study Limitationsmentioning
confidence: 95%
“…Firstly, due to our study design, it remains uncertain to what extent patients with a severe AECOPD had impairments in physical status before hospitalization. Secondly, after finalization of our study, the ROME proposal suggested an alternative classification of exacerbation severity 54 . However, we have not evaluated the specific parameters utilized in the ROME classification, leaving us uncertain about the prevalence of mild or moderate exacerbations among our patients.…”
Section: Study Limitationsmentioning
confidence: 95%
“… 11 Carmen et al applied the Rome classification to a cohort of 364 hospitalized patients with AECOPD in the Netherlands and found that the Rome classification can differentiate between exacerbation events with different short-term mortality rates. 12 The study conducted by Lee et al in Korea found excellent performance of the Rome classification for predicting ICU admission and the need for noninvasive mechanical ventilation (NIV) or IMV and acceptable performance for predicting in-hospital mortality by comparing the Rome classification with the DECAF score and GesEPOC 2021 criteria. 13 Our findings concerning the association between the Rome severity classification and the need for ICU admission and MV were highly consistent with Lee’s findings.…”
Section: Discussionmentioning
confidence: 99%
“…Similar results were also found by the two studies mentioned earlier and conducted in the Netherlands and Korea, respectively. 12 , 13 This revealed that a cutoff value of 10 mg/L may lack specificity to distinguish a moderate event from a severe one, and the mechanism linking CRP to the exacerbations of COPD may be complex and requires further researches. Probably due to the two flaws mentioned above, the Rome classification is valid in discriminating between mild and more severe AECOPD but fails to distinguish between moderate and severe AECOPD.…”
Section: Discussionmentioning
confidence: 99%
“…Secondly, we analysed the influence of comorbid CHF on BaR scoring, experienced by patients at study inclusion ( Figure 1 ) and during ECOPDs ( Figures 2 and 3 ). The only published study we know of that applies the Rome proposal on ECOPDs is the one by Reumkens et al 28 Since this study applies the Rome proposal on ECOPDs without any data on BaR, we thought it would be of particular interest to include an analysis of BaR in the present study. In these analyses, we observed no significant difference regarding BaR at study inclusion between COPD patients without CHF and those with comorbid CHF ( Figure 1 ).…”
Section: Discussionmentioning
confidence: 99%